Ethanolic extract of Casearia sylvestris and its clerodane diterpen (caseargrewiin F) protect against DNA damage at low concentrations and cause DNA damage at high concentrations in mice's blood cells - de Oliveira, Aline M. [UNESP]; Santos, André Gonzaga dos [UNESP]; dos Santos, Raquel A.; Csipak, Angelica R. [UNESP]; Olivato, Camila [UNESP]; da Silva, Isabel C. [UNESP]; de Freitas, Maura B. [UNESP]; Bassi, Carmen L.; Cavalheiro, Alberto José [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Silva, Dulce H. S. [UNESP]; Sakamoto-Hojo, Elza T.; et al. (Oxford University Press, 2009)
Casearia sylvestris is used in Brazil as a popular medicine to treat ulcer, inflammation and tumour. Caseargrewiin F is a clerodane diterpene isolated from the ethanolic leaf extract of C.sylvestris. The aim of the study was to assess the capacity of the ethanolic extract of C.sylvestris leaves and caseargrewiin F to protect DNA and verify if both the compounds cause some DNA damage, using the micronucleus (MN) test and comet assay in mice. Balb-C mice were treated with the extract [3.13, 6.25, 12.5, 25, 50 and 75 mg/kg body weight (b.w.)] and caseargrewiin F (0.16, 0.32, 0.63, 1.3, 2.5 and 3.8 mg/kg b.w.) for 14 days. on day 15, DNA damage was induced by intra-peritoneal (i.p.) injection of cyclophosphamide (CP) (i.p.) at 50 mg/kg b.w. after the MN test and comet assay were performed. A protective effect of ethanolic extract was observed in MN test (6.25 and 12.5 mg/kg b.w.) and the comet assay (3.13 and 6.25, 12.5 and 25 mg/kg b.w.). Caseargrewiin F showed protective effect at 0.63, 1.3 and 2.5 mg/kg b.w. only in comet assay. We also tested the ability of compounds of C.sylvestris to induce MN and to increase the comet assay tail moment. The experimental design was similar to the DNA protection assay except that in test groups we omitted the CP challenge. We observed increased damage at 50 and 75 mg/kg b.w. of ethanolic extract of C.sylvestris and caseargrewiin F at 3.18 mg/kg b.w. in both the MN test and comet assay. We conclude that ethanolic extract of C. sylvestris and caseargrewiin F can protect cells against DNA damage induced by CP at low concentrations, but at high concentrations these compounds also induce DNA damage.